A CLOSER STUDY OF THE DISCOURSE OF NIQABI WOMEN IN SPAIN: orígenes, sentido y dimensiones. (Journal of the Spanish Institute for Strategic Studies, 2018)
This article aims to shed some light on how niqabi women in Spainpresent and define themselves according to the meaning they attach tothe niqab. In addition, a specific objective of the study was to find outhow these women articulate, formulate and explain the niqab. For thepurpose of the study, we interviewed twelve women. The only commonrequirement for being part of the sample was to be a niqabi living inSpain. We therefore decided to use non-probability sampling. At thesame time, we employed the «snowball» sampling technique wherebythe sample was contacted in two specific ways: through differentInternet social media and using key informants to recruit participantsfor the face-to-face interviews. The interviews focused on two veryspecific questions: what meaning do the women attach to the niqab andwhat are their political, religious and social motivations for wearing it.The research findings point to growing support for the niqab andMuslim women are increasingly being encouraged to wear it.
Keywords: Niqab; niqabi women; Islam; fundamentalism; discourse analysis; Spain